2019
DOI: 10.3390/su12010333
|View full text |Cite
|
Sign up to set email alerts
|

The Antecedents of Tourists’ Behavioral Intentions at Sporting Events: The Case of South Korea

Abstract: Mega-sporting events can bring diverse benefits to the hosting areas, such as job creation and image improvement. However, only a handful of studies have explored the antecedents of destination image—which plays a crucial role in eliciting certain tourist behaviors—and personal involvement. To fill this gap, this study evaluates the relationships among personal involvement, destination image, place attachment, and behavioral intentions in the context of sporting event tourism to provide destination managers us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Facing an increasingly global competition for visitor spending, places lean on events as fundamental marketing propositions [44] in order to help individuals feel an emotional connection toward a place or destination [12,45]. The creation and delivery of emotional experiences can create brand differentiation and influence sales, loyalty and brand promotion [46].…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Facing an increasingly global competition for visitor spending, places lean on events as fundamental marketing propositions [44] in order to help individuals feel an emotional connection toward a place or destination [12,45]. The creation and delivery of emotional experiences can create brand differentiation and influence sales, loyalty and brand promotion [46].…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…The literature on event sponsorship can also be instructive in this regard. In this domain, event attitude has always been a fundamental construct for evaluating a sponsorship's effectiveness [45,52]. Ref.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…We also find studies such as the study [68] where the antecedents and moderators of the recommendation are analyzed, finding that aspects such as compromise, which is also analyzed in this study, are key. In the context of sporting events, satisfaction has been shown to be a significant predictor of future intentions to attend the event again [69][70][71]. Finally, regarding the analysis of brand image in relation to recommendation, there are studies that have analyzed the relationships that are established between variables such as perceived quality, credibility, and attitudes, as a background for loyalty that is a clear predictor of brand recommendation [72].…”
Section: Wommentioning
confidence: 99%
“…The sample profile indicated that the short-video platform users were relatively young, hence, the travel agents should fully consider the preference of youths when promoting tourism products in short-video platforms. For instance, young people prefer to take part in sports tourism [140], thus, the tourism organizations could focus on promoting this in the context of short-video platforms.…”
Section: Practical Implicationsmentioning
confidence: 99%